Immunity priming and biostimulation by airborne nonanal increase yield of field-grown common bean plants - Elizarraraz-Martínez, Iris J.; Rojas-Raya, Mariana A.; Feregrino-Pérez, Ana A.; Partida-Martínez, Laila P.; Heil, Martin (Frontiers in Plant Science, 2024)
This work reports on the effects of a treatment with nonanal on the yield of common bean plants. Yield increases were from 150 to over 400%, which we obtained with a single treatment that completely fulfils the requirements of 'organic' agriculture. The most particular aspects are that 1, All experiments have been performed with plant growing in the open field, under conditions that are realistic for smallholder farmers, 2, We have compared the effects on five different, commonly used cultivars of bean, 3, We have (partly) considered effects of resistance induction of product quality (contents of phenolic compounds and antioxidants, and the physical appearance of the grains), and 4, We have performed a cost/benefit analysis that considers the treatment costs and different prices at which the product can be sold via different venues. Therefore, we consider our work as a true 'translational' study.Scientifically, the most significant results are the observation of a growth-promotion effect and a transgenerational priming, which -in principle -opens the possibility that seed-producing companies sell 'vaccinated' seeds.